PARTICIPATION OF FPU (FORMED POLICE UNIT) 8 INDONESIA IN UNAMID IN DARFUR, SUDAN PERIOD 2016-2017 - Darajat, Iklima Tami; Tatok Djoko Sudiarto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
This study aims to analyze the involvement of Indonesian FPU (8) at UNAMID in Darfur, Sudan Period 2016-2017. To analyze the case, the author uses several concepts such as, Ethnic Conflict, Preventive Diplomacy, Humanitarian Intervention and Peace Keeping. This research is a qualitative research. The results of this study show that in an effort to muffling a protracted conflict in Darfur-Sudan, caused by the Janjaweed militia and support from Sudanese government that resulted in Ethnic Genocide on Darfur, Sudan. Seen from the prolonged conflict in Darfur, PBB issued a joint Resolution in Darfur-Sudan, called UNAMID (United Nations-African Mission in Darfur). Indonesia as a country that maintain peace feels compelled to participate in peace and security missions in Darfur- Sudan. With the agreement between the United Nations and Indonesia, Indonesia sent the FPU Police Task Force to Darfur-Sudan as a Peace Operation to stop the conflict in Darfur, Sudan. In his duty FPU 8 Indonesia as PKO, has important duties: 1) Maintain Conflict in the form of ceasefire and humanitarian protection and, 2) Conserve peace in the form of human rights and humanitarian aid.